2005
DOI: 10.1038/sj.bjc.6602804
|View full text |Cite
|
Sign up to set email alerts
|

Randomized scheduling feasibility study of S-1 for adjuvant chemotherapy in advanced head and neck cancer

Abstract: The purpose of this study was to determine the feasible adjuvant therapy administration schedule of S-1 for locoregionally advanced squamous cell carcinoma of the head and neck (SCCHN). Patients receiving definitive treatments were randomly assigned to either arm A (51 cases) receiving oral S-1 of 2-week administration followed by 1-week rest for 6 months, or arm B receiving S-1 of 4-week administration followed by 2-week rest for 6 months. Planned treatment was given in 40% of patients in arm A and 29% in arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 25 publications
4
69
0
Order By: Relevance
“…S-1 has recently been adopted as a front line chemotherapeutic regimen for the treatment of gastric cancer in Japan, based on the findings of several randomized trials. [9][10][11] Furthermore, S-1 has been also identified as an effective agent for the treatment of colorectal, 12 head and neck, 13 breast, 14 non-small-cell lung, 15 biliary tract 16 and pancreatic cancers. 17 5-FU is not used in patients with prostate cancer because of its poor efficacy and severe side effects.…”
Section: Introductionmentioning
confidence: 99%
“…S-1 has recently been adopted as a front line chemotherapeutic regimen for the treatment of gastric cancer in Japan, based on the findings of several randomized trials. [9][10][11] Furthermore, S-1 has been also identified as an effective agent for the treatment of colorectal, 12 head and neck, 13 breast, 14 non-small-cell lung, 15 biliary tract 16 and pancreatic cancers. 17 5-FU is not used in patients with prostate cancer because of its poor efficacy and severe side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of treatment. resection for gastric cancer, squamous cell carcinoma of head and neck, breast cancer and NSCLC (19,(22)(23)(24)33,34). The 5-year DFS and OS were almost the same between the S-1 group and the paclitaxel plus carboplatin group.…”
Section: Discussionmentioning
confidence: 59%
“…[18][19][20][21][22][23] Recently, Tsukuda et al reported that 2 weeks of S-1 followed by a 1-week rest period was more feasible for adjuvant chemotherapy of locoregionally advanced squamous cell carcinoma of the head and neck region than 4 weeks of S-1 followed by a 2-week rest period. 24,25 Therefore, we selected 2 weeks of S-1 followed by a 1-week rest period as the regimen for our patients.…”
Section: Discussionmentioning
confidence: 99%